A bi-stable rolling hinge for variable geometry structures. (4th June 2010) - Tupputi, Maria
A rolamite hinge is made up of two rollers held by three tensioned bands attached to either part, with ends of each band terminating on opposite sides of the hinge, ensuring a no-slip condition. This paper investigates the existence of alternative forms of the rolamite hinge by changing the profile of the rollers. The aim is to achieve a bi-stable rolling hinge that can be used to build a variable geometry structure (VGS) and stabilise it at some configurations. This hinge consists of two prismatic blocks held by three wires; each wire is continuously wrapped around circle surfaces cut into a generic cross-section of both prismatic blocks. The relationships concerned in both design and mechanical behaviour are established to provide a proper use of the hinge. However, these relationships lead to a preliminary analysis of a deeper one that it should be carried out to build a physical model.